Abstract

No abstract available.

Full Article  |  PDF Article

References

  • View by:
  • |
  • |
  • |

  1. E. Kohl, Ann. d. Physik 28, 259 (1909).
    [Crossref]
  2. See Fig. 1, triangle PP′K, where PK=P′O–PO is of the order of PK, that of the angle η, by (10).

1909 (1)

E. Kohl, Ann. d. Physik 28, 259 (1909).
[Crossref]

Kohl, E.

E. Kohl, Ann. d. Physik 28, 259 (1909).
[Crossref]

Ann. d. Physik (1)

E. Kohl, Ann. d. Physik 28, 259 (1909).
[Crossref]

Other (1)

See Fig. 1, triangle PP′K, where PK=P′O–PO is of the order of PK, that of the angle η, by (10).

Cited By

OSA participates in Crossref's Cited-By Linking service. Citing articles from OSA journals and other participating publishers are listed here.

Alert me when this article is cited.


Figures (1)

Equations (21)

Equations on this page are rendered with MathJax. Learn more.

N N 1 = β N S N 1 ,             N N 2 = β N S O ,             N 1 N 2 = β N ( S O - S N 1 ) .
S O = S N 2 / cos φ = ( S N 1 - N 1 N 2 ) / cos φ .
N 1 N 2 = β N p ( 1 - cos φ ) / ( cos φ + β N ) ,
φ r = φ - 2 β N sin φ + 2 β N 2 sin φ cos φ ,
φ r = φ - 2 α , α = β N sin φ - β N 2 sin φ cos φ .
< D O Q 1 = φ ,             P N = S N ,             P 1 O = S O ,             P P 1 = 2 N N 2 .
γ = 2 α .
sin γ / sin ( φ - γ ) = P P 1 / P 1 O = 2 N N 2 / S O = 2 β N .
tan γ = 2 β N sin φ / ( 1 + 2 β N cos φ ) = 2 β N sin φ ( 1 - 2 β N cos φ ) , γ = tan γ = 2 β N sin φ - 4 β N 2 sin φ cos φ .
η = 2 α - γ = 2 β N 2 sin φ cos φ .
P O / P 1 O = sin φ / sin ( φ - γ ) .
sin ( φ - γ ) = sin γ / 2 β N .
sin γ = γ = 2 β N sin φ ( 1 - 2 β N cos φ ) ,
P O - S O = 2 β N ( p - β N 1 - cos φ cos φ + β N ) .
P O - S O = 2 β N p = constant ,
P P / P O = sin η / sin ( φ - γ ) = 2 β N 2 cos φ , P P = 2 β N 2 P O cos φ = 2 β N 2 P O cos φ .
P O = P N 2 / cos ( φ - γ ) = ( P N 1 + N 1 N 2 ) / cos ( φ - γ ) .
P P = 2 β N 2 ( P N 1 + N 1 N 2 ) 1 - 2 β tan φ cos φ + = 2 β N 2 ( q + N 1 N 2 ) .
P P = 2 β N 2 q ( 1 + β N p q 1 - cos φ cos φ + β N ) .
P P = 2 β N 2 q = const .
F = p 0 ( 1 + β N 2 ) / 2 β N ,             R = p 0 ( 1 + β N 2 ) / β N .